Neurocognitive functions and health‐related quality of life in glioblastoma patients: a concise review of the literature. (4th November 2015) - Bergo, E.; Lombardi, G.; Guglieri, I.; Capovilla, E.; Pambuku, A.; Zagone, V.
Abstract : The maintenance of quality of life in patients with high‐grade glioma is an important endpoint during treatment, particularly in those with glioblastoma multiforme, given its dismal prognosis; thus, the primary aims of treatments are to reduce morbidity, restore or preserve neurological functions, and the capacity to perform daily activities. This review aims to summarise what is currently known about neurocognitive outcome and quality of life in patients with high‐grade glioma, particularly in glioblastoma patients. We considered all the variables that can influence neurocognitive functions, the perception of quality of life and their role as predictors for treatment outcomes.